1997
DOI: 10.1002/(sici)1097-0282(199706)41:7<703::aid-bip1>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Non-periodic lattice crystals in the hierarchical microstructure of spider (major ampullate) silk

Abstract: A commonly adopted model for the microstructure of Nephila clavipes major ampullate silk (MAS) is similar to that used for Bombyx mori (silkworm) silk: a simple composite wherein discrete, essentially perfect crystals are dispersed throughout an amorphous protein matrix. However, inconsistencies arise when researchers using complementary microstructural characterisation techniques attempt to explain their results within that framework. We present here the findings of our parallel studies in x‐ray diffraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 28 publications
8
118
0
Order By: Relevance
“…This angle was determined from simulated ␤ sheet structures with torsion angles around those observed in the DOQSY PDF. pairs are part of the larger ordered ␤ sheet regions, previously observed by electron microscopy (27). The conformation (ϯ60°, Ϯ135°) could be one of the several angle pairs of a ␤ spiral (30), but this structure is expected to show a broad range of angles (␣ F , ␤ F ) in the DECODER distribution (Fig.…”
Section: Biophysicsmentioning
confidence: 71%
See 1 more Smart Citation
“…This angle was determined from simulated ␤ sheet structures with torsion angles around those observed in the DOQSY PDF. pairs are part of the larger ordered ␤ sheet regions, previously observed by electron microscopy (27). The conformation (ϯ60°, Ϯ135°) could be one of the several angle pairs of a ␤ spiral (30), but this structure is expected to show a broad range of angles (␣ F , ␤ F ) in the DECODER distribution (Fig.…”
Section: Biophysicsmentioning
confidence: 71%
“…The poly-Ala domains have previously been characterized by NMR and x-ray and were found to be predominantly in ␤ sheet conformation (22)(23)(24) and to organize into microcrystals with sizes of at least 2 ϫ 5 ϫ 7 nm (25,26). Considerably larger domains were seen by transmission electron microscopy (27); the size of the ordered domains hints that these must incorporate some glycine. The major constituent of silk, the glycine-rich domains, has not been observed in diffraction experiments and has, in the absence of atomistic structural information, been described as an ''amorphous'' or ''rubberlike'' matrix (2,28).…”
mentioning
confidence: 99%
“…Notably, however, it is significantly smaller than the typical value of B4.8 Å observed in proteins, due to strong hydrogen bonding in the hydrophobic matrix 20,30,45,46 . Moreover, M2-M5 exhibited an additional reflection at a spacing of 5.3-5.4 Å, corresponding to the intersheet distance between stacked b-sheets observed in poly(L-alanine) 45 , spider silk (5.30 Å) 47 or related materials 20,30,46 (Fig. 3a).…”
Section: Resultsmentioning
confidence: 98%
“…11,[44][45][46][47] Comparison between the b-sheet content determined from the spectroscopic data and the percentage of amino acids that may potentially be included into the b-sheets lead to the conclusion that for the dragline fiber the AG and GGA motifs adjacent to the (A) n are incorporated into the b-sheets, 33 which is consistent with the literature. [48][49][50] Other results have shown that the minor ampullate (Mi) and cylindriform (Cyl) silks belong to the same structural family than the Ma silk as they are composed of highly oriented b-sheets (35-37%) dispersed in an amorphous matrix made of other slightly oriented secondary structures. Raman spectra have also revealed in the Mi and Cyl fibers the presence of some disordered conformations that are reminiscent of the native conformations and that are present in the dope but not in the Ma fiber.…”
Section: Determination Of the Protein Secondary Structurementioning
confidence: 99%